Complementary Contrasts in a Mobile World: 'In‐Betweenness' and the Selling of Duty‐free Products. (6th September 2016) - Weaver, Adam
Abstract: The field of tourism studies has experienced a recent 'mobility turn', a shift whereby movement of various types and via different means is seen to have become increasingly important. This paper explores relationships between mobility and sales strategies deployed by duty‐free retailers. Three in‐between conditions – between moving and waiting, between home and 'away' and between standardization and customization – have a connection with tourism‐related movement and represent contrasts deftly reconciled by duty‐free retailers. It is argued that the machinery of duty‐free selling has successfully harnessed various forms of 'in‐betweenness' associated with mass mobility for the purposes of revenue generation. Copyright © 2016 John Wiley & Sons, Ltd.